Studying dynamical models of the core galaxy NGC 1399 with merging remnants. (December 2018) - Yeh, Li-Chin; Jiang, Ing-Guey
Abstract: An investigation on the possible dynamical models of the core galaxy NGC 1399 is performed. Because early-type galaxies are likely to be formed through merging events, remnant rings are considered in the modeling process. A numerical survey over three parameters is employed to obtain the best-fit models that are completely consistent with observations. It is found that the inner slope of the dark matter profile is cuspy for this core galaxy. The existence of remnant rings in best-fit models indicates a merging history. The remnant ring explains the flattened surface brightness and thus could be the physical counterpart of the core structure of NGC 1399.